To Analyse The Impact of “Build-Then-Sell 10:90 Variant” (BTS) System From The Aspect of House Buyers - Tang, Siang Peng (Universiti Sains Malaysia, 2007)
Under the current housing delivery system, house buyers are always the parties who carry the financial risk. Though the market has been adopting the Sell-Then-Build system for the past few decades, it does not make it a rightful system. Sell-Then-Build system is an unfair approach to housing delivery as it greatly favours developers instead of house buyers. House buyers are the parties who are least protected and who have absolutely no power to control the situation, behaviour and activities of the developers.